Peran Keluarga Terhadap Self Management Pasien Pasca Stroke: Literature Review - Yuniarti, Irmina Ika; Kariasa, I Made (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Stroke cause mortality and impact due to stroke. Self management with family support is needed to adapt topost stroke conditions and prevent recurrent stroke. family support has a role for self management success.Objective: the literature review aims to identify and analyze the important role of family support for selfmanagement stroke patients. Design : narrative literature review. Methods : study analysis published on theon line data base : ProQuest, EBSCO, Google Scholar and Scopus. The study was selected using the criteriaand keywords for the 2015-2019 period. Nine studies were analyzed using literature review process. Results:Family support that can be given to stroke patients in carrying out self management includes : support fordisease management, management roles and emotional management. Conclusion: Family support is neededto improve stroke self management. The family is the main companion of the of the adapting to changes afterstroke.